Enhancing Cognitive Stimulation with Coffee: A Pathway to Heightened Mental Performance - Maspul, Kurniawan Arif (Edutech Publishing Media, 2024)
This article discusses the potential of coffee as a cognitive enhancer. The aim of this research is to explore the cognitive benefits of coffee use by qualitatively utilizing relevant ideas and empirical facts. The research method employs a qualitative study approach that includes interviews, observations, and literature review. The results of the study show that individuals looking to improve their cognitive performance through coffee use are given practical advice. Furthermore, this research proposes a strategy to widen the societal influence of coffee-stimulated cognitive activity. The conclusions of this research allow readers to properly exploit the cognitive benefits of coffee by using new methods and creating broad awareness of the topic. It emphasizes the need for future research in various areas such as long-term effects, individual differences, synergistic techniques, and specific cognitive domains to maximize the potential of coffee as a cognitive enhancement tool and promote cognitive well-being in society. The contribution of this research provides practical guidelines for individuals to leverage coffee in enhancing cognitive performance.